A novel balance training approach: Biomechanical study of virtual reality-based skateboarding - Kantha, P.; Hsu, W.-L.; Chen, P.-J.; Tsai, Y.-C.; Lin, J.-J. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The use of virtual reality (VR) technology in training and rehabilitation gained increasing attention in recent years due to its potential to provide immersive and interactive experiences. We developed a novel VR-based balance training, VR-skateboarding, for improving balance. It is important to investigate the biomechanical aspects of this training, as it would have benefited both health professionals and software engineers.